Pengaruh GDP Per Kapita, dan Konsumsi Energi Terhadap Emisi CO2 di Indonesia - Ikramina Salsabila Nur Amalina; Heru Wahyudi; Ukhti Ciptawaty (Journal on Education, 2023)
This study aims to analyze the effect of GDP Per Capita and Energy Consumption on Carbon Dioxide Emissions in Indonesia in the short and long term. This study uses the Error Correction Model (ECM) method. The ECM method is used to find out how the long-term and short-term influances of the variables that affect carbon dioxide emissions. In addition, this study uses time series data in the form of annual from 1992 to 2021. The results show that the variables GDP per capita and Energy Consumption have a positive and significant effect on carbon dioxide emission in the long and short term.